2012
DOI: 10.4028/www.scientific.net/ast.80.142
|View full text |Cite
|
Sign up to set email alerts
|

Classified Catalogue for Textile Based Sensors

Abstract: Technical textiles are used primarily for their technical functionality in many different industries. For monitoring the functionality of textiles it is possible to integrate sensors into the textile. Since textiles are made of fibres, yarns, two-or three dimensional structures the sensor systems should accordingly be designed as a part of them. Smart textiles are concerned with textile based sensors integrated mechanically and structurally to a textile. The state of the art in developing textile based sensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Recently, many studies have reported the manufacture of smart wear capable of measuring bio-signals (heart rate, respiration rate, and movement) [6]. Among them, EMG electrodes that can measure muscle activity have been used for training to improve the rehabilitation effect of professional athletes or prevent injuries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have reported the manufacture of smart wear capable of measuring bio-signals (heart rate, respiration rate, and movement) [6]. Among them, EMG electrodes that can measure muscle activity have been used for training to improve the rehabilitation effect of professional athletes or prevent injuries [7].…”
Section: Introductionmentioning
confidence: 99%
“…Integrating electronic components and circuits into textiles can be distinguished in three different levels: textile‐adapted, textile‐integrated, and textile‐based. [ 8 ] The first and simplest level of integration is to mount electronic devices onto a garment, e.g., the first wearable computer by Edward Thorp in 1961. [ 9 ] In earlier developments, space for a headphone cord was provided inside a garment, or the handsfree was preinstalled so the user could easily connect an MP3 player or other musical devices to enjoy music on the go.…”
Section: Introductionmentioning
confidence: 99%